Dinamika Pembiayaan Perbankan Syariah Dalam Mengembangkan Dunia Usaha - Kasmiati Kasmiati (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2021)
his paper aims to analyze the development of financing that has been carried out by Islamic banking, both Islamic Commercial Banks (BUS) and Sharia Business Units (UUS). The analysis focuses on fluctuations in the value of the financing that has been disbursed based on the type of use and based on the contract used. This analysis is carried out using a quantitative approach with secondary data in the form of statistical financial statements of BUS and UUS for the period 2014 – 2018 obtained from the Directorate of Islamic Banking of Bank Indonesia and the Financial Services Authority. The performance of Islamic banking, especially BUS and UUS, on a macro basis is quite encouraging. This achievement is shown by the increasing growth rate of financing and distribution of working capital and investment which tends to increase every year. However, the distribution of this financing is dominated by the distribution of non-SME business types. In addition, the allocation of financing distribution aimed at consumption has experienced very fast growth so that the portion of financing to support the productive sector has decreased. Another weakness is that the portion of financing is still dominated by financing with the murabahah scheme, and is channeled to the non-SME business level.